2021
DOI: 10.1101/2021.06.04.447091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enviromic assembly increases accuracy and reduces costs of the genomic prediction for yield plasticity

Abstract: Quantitative genetics states that phenotypic variation is a consequence of genetic and environmental factors and their subsequent interaction. Here, we present an enviromic assembly approach, which includes the use of ecophysiology knowledge in shaping environmental relatedness into whole-genome predictions (GP) for plant breeding (referred to as E-GP). We propose that the quality of an environment is defined by the core of environmental typologies (envirotype) and their frequencies, which describe different z… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 77 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…Enviromics is the large-scale envirotyping, based on the collections of environmental data across time and space to establish a global association between the crops envirome (the core of TPEs) and phenotypic variation of key factors driving G×E. From enviromics, it is possible to derive some useful outputs, such as an environmental relatedness matrix, which supposes that the core of typologies is a marker of "environmental polymorphisms" (Resende et al 2020, Costa-Neto et al 2021a, Costa-Neto et al 2021c. Another important goal of enviromics is its further integration in systems biology approaches, which can support the understanding of genomics × enviromics interactions, but also its relation with different omics sources (e.g., transcriptomic, proteomic) and its impact on improving accuracy and resolution of predictive breeding platforms (Costa-Neto et al 2021a, Costa-Neto et al 2021b, Rogers et al 2021.…”
Section: What Is Genotype By Environment Interaction?mentioning
confidence: 99%
See 4 more Smart Citations
“…Enviromics is the large-scale envirotyping, based on the collections of environmental data across time and space to establish a global association between the crops envirome (the core of TPEs) and phenotypic variation of key factors driving G×E. From enviromics, it is possible to derive some useful outputs, such as an environmental relatedness matrix, which supposes that the core of typologies is a marker of "environmental polymorphisms" (Resende et al 2020, Costa-Neto et al 2021a, Costa-Neto et al 2021c. Another important goal of enviromics is its further integration in systems biology approaches, which can support the understanding of genomics × enviromics interactions, but also its relation with different omics sources (e.g., transcriptomic, proteomic) and its impact on improving accuracy and resolution of predictive breeding platforms (Costa-Neto et al 2021a, Costa-Neto et al 2021b, Rogers et al 2021.…”
Section: What Is Genotype By Environment Interaction?mentioning
confidence: 99%
“…Similar to the classical GBLUP, in which molecular markers shape a genomic relationship matrix (G), the environmental relatedness must also be created using the linear covariance among W covariates (W). In addition, the authors showed a more intuitive approach to model G×E, in which now the Hadamard product (#) between genomics, GW~ZgGZg T # ZeWZe T, and what was called later as 'enviromic-based matrix' (Costa-Neto et al 2021a, Costa-Neto et al 2021c) is the core of putative reaction-norms driving the expected G×E (Jarquin et al 2014). This approach was expanded by Morais-Júnior et al ( 2018), which involved a wide number of W covariates and another genetic relatedness, both from genomics and pedigree-based records.…”
Section: Adding Value To the Classical Predictive Breeding Platformsmentioning
confidence: 99%
See 3 more Smart Citations